Tindak Tutur Ilokusi dalam Media Digital Program Catatan Najwa Edisi Perempuan - Naila Salma; Latifatul Ni’mah; Lutfi Anifatun Wahidah; Rayna Amalia Putri; Chandra Hadi Cipto Nugroho; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Lukman Alfaris (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2026)
This study is motivated by the increasing use of social media as a space for discussion and the exchange of ideas, as exemplified by the program Catatan Najwa: “Women” Edition, which demonstrates a diversity of meaningful speech acts. In pragmatic studies, illocutionary speech acts are a crucial aspect to examine because they reflect the speaker’s intentions and the functions of the utterances conveyed. This study aims to describe the forms of illocutionary speech acts found in the Catatan Najwa program, “Women” Edition. This study employs a descriptive-qualitative method using non-participatory observation, known as Simak Bebas Libat Cakap or SBLC, and note-taking techniques. The results of this study indicate that several forms of illocutionary speech acts are found, including assertive, directive, expressive, and commissive speech acts. Assertive speech acts are the most dominant form, functioning to state, report, and affirm information. This study is expected to contribute to the development of pragmatic studies, particularly regarding illocutionary speech acts in digital media.